Regulatory Mechanisms of Autophagy-Targeted Antimicrobial Therapeutics Against Mycobacterial Infection - Silwal, Prashanta; Paik, Seungwha; Kim, Jin Kyung; Yoshimori, Tamotsu; Jo, Eun-Kyeong (Frontiers in Cellular and Infection Microbiology, 2021)
Mycobacterium tuberculosis (Mtb) is an intracellular pathogen causing human tuberculosis, an infectious disease that still remains as a global health problem. Autophagy, a lysosomal degradative process, has emerged as a critical pathway to restrict intracellular Mtb growth through enhancement of phagosomal maturation. Indeed, several autophagy-modulating agents show promise as host-directed therapeutics for Mtb infection. In this Review, we discuss recent progress in our understanding the molecular mechanisms underlying the action of autophagy-modulating agents to overcome the immune escape strategies mediated by Mtb. The factors and pathways that govern such mechanisms include adenosine 5′-monophosphate-activated protein kinase, Akt/mammalian TOR kinase, Wnt signaling, transcription factor EB, cathelicidins, inflammation, endoplasmic reticulum stress, and autophagy-related genes. A further understanding of these mechanisms will facilitate the development of host-directed therapies against tuberculosis as well as infections with other intracellular bacteria targeted by autophagic degradation.